Propuesta de modelo predictivo del precio del pan mediante uso RNA. “Un caso de estudio sector panificador, Bogotá” (2023)
The main purpose of this study is to use a model based on neural networks artificial intelligence (RNA) programmed in Python through Google Colaboratory as an environment of execution, to predict the price of bread. The purpose is to offer a projection reasonable demand, which can be used in the formulation of strategies and production techniques for the baking sector, with the aim of improving efficiency and effectiveness of processes or optimize decision making in the business model of the future price of bread. Likewise, it is expected that this research will identify different challenges related to the increase in bread prices.